Adaptive Concrete Beams Equipped With Integrated Fluidic Actuators - Christian Kelleter; Timon Burghardt; Hansgeorg Binz; Lucio Blandini; Werner Sobek (Frontiers in Built Environment, 2020)
The rapidly growing world population is a great challenge for the building industry. Due to the impending scarcity of resources, it is not possible to provide the growing mankind with sufficient living and work places and infrastructure with current construction methods. For wide-spanning beams and slabs, the decisive design criteria are mainly determined by deformations rather than stresses, since deflections must be limited. This leads to structural elements, which are not fully utilized. However, if the deformations can be reduced, significant material savings can be achieved. Sensors, actuators, and a control unit enable components subjected to bending to adapt to high but rare loads. This article presents a solution that allows beams to react actively to loads by use of integrated actuators. The newly developed integrated hydraulic actuators allow the structure to react specifically to a wide range of load cases, by adjusting the internal hydraulic pressure. This is a clear advantage in load-bearing systems because there is often no dominant load case. This internal actuation concept is a new approach, as previous adaptive structures either have externally added actuators or are composed of truss structures in which single bars are actuated. In this paper, the concept is explained analytically, simulated with the finite element method and validated experimentally.